Effectiveness of extracorporeal shockwave therapy for chronic Achilles tendinopathy: A randomized clinical trial - Babak Vahdatpour; Hadi Forouzan; Fatemeh Momeni; Mehdi Ahmadi; Parisa Taheri (Journal of Research in Medical Sciences, 2018)
Background: In this study, we aimed to evaluate the effectiveness of extracorporeal shockwave treatment (ESWT) on pain and ankle-hindfoot scale of the American Orthopedic Foot and Ankle Society (AOFAS) score of patients with chronic Achilles tendinopathy (AT). Materials and Methods: In this double-blind clinical trial, 43 patients with chronic AT were selected and randomly allocated in two groups to receive a basic treatment with ESWT or sham SWT (radial and focused shock waves, four sessions once a week for 4 weeks). AOFAS and pain scores for each patient were recorded at baseline (before intervention), immediately after intervention, and 4 and 16 weeks after intervention using AOFAS and visual analog scale (VAS) scaling method. Results: A total of 43 patients (22 ESWT and 21 sham SWT) were participated in this study. Both groups improved during the treatment and follow-up period. The mean VAS score decreased from 7.55 to 3 in the intervention group and from 7.70 to 4.30 in the sham SWT group. Mean AOFAS and VAS scores were significantly different between ESWT and no ESWT groups at 16 weeks of follow-up (P = 0.013) (P = 0.47). There was no significant difference in terms of AOFAS and VAS scores between both the groups in the other follow-up times. Conclusion: Overall, ESWT causes decrease in VAS score and increase in AOFAS score. However, due to the small sample size, the results were not statistically significant. It is recommended to plan more interventional studies with larger sample size in the future.